Formulasi Kapsul Ekstrak Etanol Daun Sambung Nyawa (Gynurae procumbens (Lour) Merr) dengan Variasi konsentrasi Bahan Pengikat Polivinil Pirolidon (PVP) - burhan, Asril; Ikbal; Zulham, Zulham; Aisyah , Andi Nur; Khairi, Nur; Ulfa, Maria (Media Farmasi, 2024)
Formulation of Ethanol Extract Capsules of Sambung Nyawa Leaves (Gynurae procumbens (Lour) Merr) with Varying Concentrations of Polyvinyl Pyrrolidone (PVP) Sambungnyawa (Gynurae procumbens (Lour) Merr) is known to have several secondary metabolite compounds including alkaloids, flavonoids, anthraquinones, saponins, glycosides and essential oils. The aim of this research is to obtain a stable concentration of PVP binder if formulated in granule form for encapsulation in ethanol extract of sambungjiwa leaves. The variation in PVP concentration used was 0.5%; 1.5 %; 2.5 %; 3.5 %; and 4.5%. Granules are made using the wet granulation method then put into the capsule shell and continued with evaluation. Based on the evaluation results of the ethanol extract capsule formulations of sambungjiwa leaves, it can be concluded that variations in the concentration of PVP as a binder can affect the physical stability of the capsule preparation, where the five formulas with different concentration variations have different stability after hygroscopicity testing. The formula that has good physical stability is the FK4 formula with a PVP concentration of 3.5%. Sambung Nyawa (Gynurae procumbens (Lour) Merr) diketahui memiliki beberapa senyawa metabolit sekunder diantaranya alkaloid, flavonoid, antraquinon, saponin, glikosida dan minyak atsiri, Tujuan dari penelitian ini untuk mendapatkan konsentrasi bahan pengikat PVP yang stabil jika diformulasi dalam bentuk granul untuk dikapsulkan pada ekstrak etanol daun Sambung Nyawa. Variasi konsentrasi PVP yang digunakan adalah 0,5 %; 1,5 %; 2,5 %; 3,5 %; dan 4,5 %. Granul dibuat dengan metode granulasi basah kemudian dimasukkan ke dalam cangkang kapsul dan dilanjutkan dengan evaluasi. Berdasarkan hasil evaluasi dari formulasi kapsul ekstrak etanol daun Sambung Nyawa  dapat disimpulkan bahwa variasi konsentrasi PVP sebagai bahan pengikat dapat mempengaruhi kestabilan fisik sediaan kapsul, dimana kelima formula dengan variasi konsentrasi yang berbeda memiliki kestabilan yang berbeda-beda setelah pengujian higroskopisitas. Formula yang memiliki kestabilan fisik yang baik adalah formula FK4 dengan konsentrasi PVP 3.5%.